Answer:
Step-by-step explanation:
Given Equation :
[tex] \qquad \sf \dashrightarrow \: 3(4x+3) = 2x - 5(3 - x) + 2[/tex]
Using distribute property:
[tex]\qquad \sf \dashrightarrow \: 12x + 9 = 2x - 15 + 5x + 2[/tex]
Adding the like terms we get :
[tex]\qquad \sf \dashrightarrow \: 12x + 9 = 2x + 5x - 15 + 2[/tex]
[tex]\qquad \sf \dashrightarrow \: 12x + 9 = 7x - 13[/tex]
Transposing the variables on the right side and constant terms on the left side :
[tex]\qquad \sf \dashrightarrow \: 12x - 7x = - 13 - 9[/tex]
[tex]\qquad \sf \dashrightarrow \: 5x = - 22[/tex]
Dividing both sides by 5 :
[tex]\qquad \sf \dashrightarrow \: \dfrac{5x}{5} = \dfrac{ - 22}{5} [/tex]
[tex]\qquad \bf \dashrightarrow \: x = \dfrac{ - 22}{5} [/tex]